Variation of antlers in individual red deer (Cervus elaphus) stags: repeatability, age and side effects - Bils, Katharina; Willems, H.; Reiner, G.; Justus Liebig University Giessen (My University, 2023)
Antlers are formed anew each year to realise an optimal relationship between their size and weight and the physical body condition in Cervidae. This results in the objective to match fighting abilities with size and mechanical performance of the antlers, as well as to advertise these correlated abilities to other males and females. The resulting variation in individual antler characteristics from year to year can show considerable differences. To characterise and understand these differences is important in hunting, game management and deer breeding, as well as potentially to assess the habitat quality. However, relatively few traits of the antler have been scientifically tested for this purpose, and only a few studies were conducted on the same individual in free-ranging red deer over the years. The objective of the present study was to quantify the influence of the individual (repeatability), the age and the site on the expression of 125 antler characteristics. For this purpose, we collected 35 stags with an average of about 10 consecutive antlers per individual (confirmed by genetic analysis), a total of 355 antlers. The antlers were scanned 3-dimensionally and measured semi-automatically. Numbers, lengths, distances, circumferences, bending, curvatures, angles, forms and CIC (International Council for Game and Wildlife Conservation) characteristics were compiled and evaluated in a generalised linear mixed model adapted to the distribution of the characteristics. The complete model explained 1.6 to 83% of character variation. Mean repeatability of the characteristics varied between 2.7 and 74.4%. The stags’ age explained 0 to 36.4%, and the side explained 0 to 2.5% of the variability. Some characteristics of burr, signet, beam and the lower tines reached the highest repeatability; the highest variability was found in characteristics of the crown. Values of 11 features that are frequently used in other studies corresponded very well with the present study. However, some features reached higher repeatability every year, whereas others varied more closely with age. Such characteristics might be selectively included into further research or practical applications to increase informative value.
Keywords: ddc:630